2007
DOI: 10.1128/aem.01840-06
|View full text |Cite
|
Sign up to set email alerts
|

A Five-Strain Probiotic Combination Reduces Pathogen Shedding and Alleviates Disease Signs in Pigs Challenged with Salmonella enterica Serovar Typhimurium

Abstract: Salmonella spp. infection is a major cause of gastroenteritis, with many thousands of cases reported in the European Union every year. The use of probiotics offers the potential to improve this situation. Here, we investigate the effects of oral treatment of pigs with a defined lactic acid bacteria culture mixture on both clinical and microbiological signs of Salmonella enterica serovar Typhimurium infection. Fifteen weaned pigs blocked by sex and weight were administered control milk or a mixture of five prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
150
1
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(159 citation statements)
references
References 26 publications
2
150
1
6
Order By: Relevance
“…On the other hand, Szasz, (2002), Ware and Zinn (2005) reported that Fibrozyme inclusion to the steers or heifer's diets increased total tract digestibility of NDF and ADF and increased DMI and average daily gain. Few workers concluded improved feed intake, feed conversion rate, daily weight gain and total body weight in sheep, goat and cattle on administration of DFM (Torres-Rodriguez et al, 2007;Samli et al, 2007;Casey et al, 2007). Improvement from DFM supplementation could be anticipated due to positive effects on various digestive processes, especially cellulolysis, synthesis of microbial protein, stabilizers of ruminal pH and lactate, increased absorption of some nutrients and displayed a growth-promoting effect.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Szasz, (2002), Ware and Zinn (2005) reported that Fibrozyme inclusion to the steers or heifer's diets increased total tract digestibility of NDF and ADF and increased DMI and average daily gain. Few workers concluded improved feed intake, feed conversion rate, daily weight gain and total body weight in sheep, goat and cattle on administration of DFM (Torres-Rodriguez et al, 2007;Samli et al, 2007;Casey et al, 2007). Improvement from DFM supplementation could be anticipated due to positive effects on various digestive processes, especially cellulolysis, synthesis of microbial protein, stabilizers of ruminal pH and lactate, increased absorption of some nutrients and displayed a growth-promoting effect.…”
Section: Discussionmentioning
confidence: 99%
“…A common report from producers experiencing JHS outbreaks in cattle is the ineffectiveness of antibiotic treatments [3,4] providing the impetus to develop novel approaches to managing mycotoxicoses. In monogastric livestock, probiotic and prebiotic feed additives mitigate pathogen issues in a number of ways including establishing beneficial bacteria in the intestinal tract [8,9], improving the ability of the mucosa to withstand infection [10,11,12], improving the defense system [8,9], binding toxins [3,4,13] and interfering with pathogen colonization sites [3,4,14]. Probiotics can improve milk production and rumen function in goats [15][16][17][18][19][20][21] with a 280-head commercial dairy herd were used in the study.…”
Section: Introductionmentioning
confidence: 99%
“…Among others, the use of probiotics such as lactobacilli and bifidobacteria has been proposed as the most promising approach for maintaining or improving animal health (Stein and Kil, 2006;Lalles et al, 2007). It has been reported that feeding certain probiotic strains to pigs could improve growth performance, prevent the growth of pathogenic bacteria and reduce the incidence of diarrhea (Shu et al, 2001;Gardiner et al, 2004;Taras et al, 2006;Casey et al, 2007). At the same time, feeding an FLD prepared with the use of bacteria, such as lactic acid bacteria, has also been shown to improve pig performance and to reduce the number of enteric pathogens (Canibe and Jensen, 2003;Stein and Kil, 2006).…”
Section: Introductionmentioning
confidence: 99%